MILLION Study - Nichols, Emma Hitt (MD Conference Express, 2015)
The MILLION study shows that aggressive, simultaneous treatment with an amlodipine- and statin-based regimen lowers blood pressure and low-density lipoprotein cholesterol to a greater extent than standard intensity treatment in a Japanese population. However, percent change in coronary plaque volume, and lumen and vessel volume were similar among both treatment arms.